Integrative physiological and biomechanical aspects in competitive cross-country skiing - Holmberg, H. C. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
Cross-country skiing involves a large variety of skiing techniques. Among these double poling (DP) has markedly increased in importance during the last decade, accentuated by new racing events with higher racing velocity. The aims with the present studies were to describe DP using an integrative physiological and biomechanical approach.